Moving gender: Home museums and the construction of their inhabitants. Issue 3 (August 2019) - Vinitzky-Seroussi, Vered; Dekel, Irit
Home museums in Israel and Germany produce a representational space in which the public figure, usually a 'great man, ' is effectively 'dragged home' to the so-called private sphere so as to make the domestic worthy of musealization. Based on three years of ethnographic research in nine such museums (four in Israel and five in Germany), this article shows that when the sphere most identified with women is represented through the life and work of the men who lived there, the place of the wife and children is sidelined, belittled, and at times concealed. In representing famous persons through material space and objects in the private abode, museal techniques determine which specific domestic areas, such as the kitchen and the bedroom, become the prime location of telling stories about women who lived in the house. They provide a shared perspective for visitors who find the stories about the wives endearing, recognizing home through them.